Editorial: Seeking the Benefits of Broadband - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2021)
This editorial comes in three parts: some observations on national preparedness to capture the benefits of widespread broadband availability; some updates on the editorial team that produces the Journal of Telecommunications and the Digital Economy; and a brief introduction to the papers in this issue.